Thoracic aorta and coronary artery calcificationin patients referred to myocardial perfusion scintigraphy - Štalc, Monika (Medicinski razgledi (Supplement), 2024)
BACKGROUNDS. Myocardial perfusion imaging (MPI) is a well-established non-invasive imaging technique for the diagnosis of coronary artery disease (CAD). MPI may detect obstructive CAD but fail to discover subclinical atherosclerosis. With advances in technology, low-dose CT for attenuation correction has become an important part of nuclear cardiology. CT in MPI allows for the visualization of thoracic aorta calcification (TAC) and coronary artery calcification (CAC). The aim of the study was to evaluate the prevalence of TAC and CAC in patients referred to MPI. METHODS. Clinical characteristics, MPI results, and prevalence of CAC and TAC were collected from 90 consecutive patients with an intermediate likelihood of CAD and without previously known atherosclerosis who were admitted to MPI. RESULTS. Out of 90 patients, 32 (35.6%) had ischemia, and 58 (64.4%) patients had normal MPI. Calcification was present in 63.3% of all patients on low-dose CT (75.0% with ischemia versus 57.0% with normal MPI, p = 0.09). Most patients with CAC had concomitant TAC. In more than a quarter of patients, only TAC was present. More patients with ischemic MPI had CAC compared to patients with normal MPI (53.1% versus 25.8%, p = 0.01). Patients with normal MPI and TAC or CAC were older (71.1 ± 7.6 years versus 56.5 ± 9.2 years, p < 0.001) and had more arterial hypertension (78.9% versus 52.0%, p = 0.03) than patients without calcification. Patients with normal MPI and suffering only from TAC had more arterial hypertension than patients with CAC (94.4% versus 60.0%, p = 0.01). CONCLUSIONS. The combination of myocardial perfusion, CAC, and TAC from a single MPI scan may have a complementary role in the management of patients with an intermediate risk of CAD. In addition to improving risk estimation, reporting visually estimated calcification may influence patient management decisions.
Keywords: kalcifikacija torakalne aorte; koronarna kalcifikacija; miokardna perfuzijska scintigrafija; računalniška tomografija